Knowledge and attitude on sunnah food and Islamic eating practices among students Universiti Malaysia Sabah - Mariam Abdul Latif; Suhaimi Ab. Rahman (HH Publisher, 2020)
The preservation of future generation and the protection of consumer welfare is a priority in view of the progressive negative behaviours existing in today’s societies at large. This study aims to evaluate the level of knowledge and attitude on sunnah food and Islamic eating practices, and to determine the relationship between knowledge, attitude and practices among students from Universiti Malaysia Sabah (UMS). The study involved around 414 respondents through convenience sampling by using questionnaires as the research instrumentation. The data was analysed by using SPSS version 25. This study highlighted that family is the main reference for source of information on halal food products followed by the internet and lecturer. Most members of the faculties at UMS has high level of knowledge on the concept of halal and haram in halal food, followed by the Islamic law (Sharia’) on halal food and beverages. This is due to courses on halal and haram foods being offered at various faculties in UMS. Although the majority of respondents has high level of knowledge on sunnah food, but the practices of respondents consuming the sunnah food is low. This happens because the fruits such as dates, pomegranates and figs are quite expensive and not easily accessible in the city of Kota Kinabalu. The study found that the Muslim respondents have positive attitude (i.e. proven by satisfactory level) towards sunnah food and eating practices: (1) they always choose sunnah and tayyib food whenever they want to eat; (2) they eat in congregation (with friends or family) when they want to eat; (3) washing hands before and after eating; (4) saying “Bismillah” before eating ; (5) sharing food with friends. However, some of the eating practices are not encouraged by Islam, but because it has become a custom or a part of their daily eating practices. This happens because the Malaysian public is not familiar with eating food from the Arab countries, where it was a way of life for the Prophet SAW. Results also showed that the knowledge on Sunnah food was significantly correlated with attitude (r = 0.217; p < 0.05) and practices (r = 0.085; p < 0.05) of the UMS students showing positive linear correlations, which confirms that better knowledge can lead to positive attitude and subsequently in good practices.